2018
DOI: 10.1136/bjsports-2018-099191
|View full text |Cite
|
Sign up to set email alerts
|

Effects and moderators of exercise on muscle strength, muscle function and aerobic fitness in patients with cancer: a meta-analysis of individual patient data

Abstract: Exercise interventions during and following cancer treatment had small effects on UBMS, LBMS, LBMF and aerobic fitness. Demographic, intervention-related and exercise-related characteristics including age, marital status, intervention timing, delivery mode and frequency and type and time of exercise sessions moderated the exercise effect on UBMS, LBMS and aerobic fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 76 publications
6
43
1
Order By: Relevance
“…Furthermore, patients in this study who completed the Chester Step Test were significantly younger and had less comorbidity than patients who did not complete the test. The mean hand grip strength for women and men in this study was comparable to the grip strength found in healthy elderly [33] and in slightly younger patients with different types of cancer during or after treatment [31]. The 14 times standing during the 30-second chair-stand test, was slightly lower than the 17 times reported in patients during or following treatment for different types of cancer [31], which might be explained by the younger age in the latter study.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Furthermore, patients in this study who completed the Chester Step Test were significantly younger and had less comorbidity than patients who did not complete the test. The mean hand grip strength for women and men in this study was comparable to the grip strength found in healthy elderly [33] and in slightly younger patients with different types of cancer during or after treatment [31]. The 14 times standing during the 30-second chair-stand test, was slightly lower than the 17 times reported in patients during or following treatment for different types of cancer [31], which might be explained by the younger age in the latter study.…”
Section: Discussionsupporting
confidence: 67%
“…The mean hand grip strength for women and men in this study was comparable to the grip strength found in healthy elderly [33] and in slightly younger patients with different types of cancer during or after treatment [31]. The 14 times standing during the 30-second chair-stand test, was slightly lower than the 17 times reported in patients during or following treatment for different types of cancer [31], which might be explained by the younger age in the latter study. Overall, results showed that newly diagnosed patients with HNC before treatment have lower levels of physical activity, cardiorespiratory fitness and lower body muscle function compared with the general population and survivors with various types of cancer, but comparable hand grip strength.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Patients may underestimate how the treatment might affect their ability to exercise on their own. Also, current evidence indicates that exercise under supervision yields better outcomes . Therefore, even for currently active patients, regular evaluation of activity levels is needed, and referral to exercise programming could be valuable.…”
Section: What Oncology Clinicians Can Do Now: Assess Advise and Refermentioning
confidence: 99%
“…Also, current evidence indicates that exercise under supervision yields better outcomes. 10,[43][44][45][46][47] Therefore, even for currently active patients, regular evaluation of activity levels is needed, and referral to exercise programming could be valuable. The provider's willingness to discuss exercise during patient visits expresses confidence in the benefits of regular exercise during and after treatment.…”
Section: Step 3: Refermentioning
confidence: 99%